2016
DOI: 10.1016/j.pmedr.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of objectively-measured physical activity and sedentary time over the course of pregnancy in women self-identified as inactive

Abstract: There is a need for investigations that document the daily course of pregnancy-related changes in PA and sedentary behavior. The purpose of this study was to describe the trajectory of PA and sedentary behavior and whether they differ among weight status in pregnant women self-identified as inactive. Eighty inactive pregnant women (8–16 weeks) were recruited from a nationwide text-message intervention. PA was measured using a Fitbit. Chi-square analyses and t-tests were used to analyze univariate demographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 49 publications
(91 reference statements)
4
56
2
4
Order By: Relevance
“…It should be noted though that this risk remains modest and that our large sample partly contributed to finding significant associations. Importantly, and consistent with previous cross-sectional studies (30,31), household/caregiving activities constituted the largest source of physical activity energy expenditure in our population. It has been suggested that household activities, in comparison to leisure-time activities, are not usually performed for enjoyment or by choice and could be stressful or burdensome, thereby contributing to women's depressive symptoms (10,32).…”
Section: For Every Additional 30 Minutes Per Week Of Household and Casupporting
confidence: 91%
See 1 more Smart Citation
“…It should be noted though that this risk remains modest and that our large sample partly contributed to finding significant associations. Importantly, and consistent with previous cross-sectional studies (30,31), household/caregiving activities constituted the largest source of physical activity energy expenditure in our population. It has been suggested that household activities, in comparison to leisure-time activities, are not usually performed for enjoyment or by choice and could be stressful or burdensome, thereby contributing to women's depressive symptoms (10,32).…”
Section: For Every Additional 30 Minutes Per Week Of Household and Casupporting
confidence: 91%
“…A further key finding from this study is that women who engage in more sedentary behaviors at the end of their pregnancy have an increased likelihood of postpartum depression. This is of particular importance given the fact that pregnant women spend at least 70% of time awake in sedentary behaviors (34) and that sedentary time increases even in those that maintain recommended physical activity levels during pregnancy (30). We are aware of only one other study that examined the association between sedentary behavior in pregnancy and postpartum depression risk.…”
Section: For Every Additional 30 Minutes Per Week Of Household and Camentioning
confidence: 99%
“…Our results reflect the well-documented provider-patient communication gap on GWG. 12,14,15 Providers recalled discussions and reported distributing educational materials more than patients recalled receiving them. Patients may expect significant GWG during pregnancy and may not know the potentially harmful effects it can have on their own and their child's health, leading providers to report higher levels of discussions on GWG since they are aware of these adverse health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 The Center for Disease Control and Prevention (CDC) applied the 2009 IOM recommendations to GWG data collected across the United States in 2012 and 2013 and found only 32.1% of pregnant women gained an appropriate amount of weight. 11 Many factors likely contribute to this concerning health issue, including levels of activity during pregnancy, 12,13 incorrect provider recommendations, 14 or a providerpatient communication gap. 15 Wrotniak et al 16 found only 54.8% of patients received GWG recommendations consistent with IOM guidelines from their provider.…”
mentioning
confidence: 99%
“…However, prior studies of ATD use in pregnancy have not evaluated sleep duration. [4][5][6] The primary objective of this study was to describe sleep duration, as measured by the main sleep event in a 24-hour period, across gestation in women who wore a commercially available ATD during pregnancy. A secondary objective was to study the association between sleep duration and adverse maternal and neonatal outcomes such as excessive gestational weight gain, pregnancy associated hypertension, and birthweight.…”
mentioning
confidence: 99%